If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 5) = 3x + 15 Reorder the terms: -1(5 + x) = 3x + 15 (5 * -1 + x * -1) = 3x + 15 (-5 + -1x) = 3x + 15 Reorder the terms: -5 + -1x = 15 + 3x Solving -5 + -1x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + -1x + -3x = 15 + 3x + -3x Combine like terms: -1x + -3x = -4x -5 + -4x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + -4x = 15 + 0 -5 + -4x = 15 Add '5' to each side of the equation. -5 + 5 + -4x = 15 + 5 Combine like terms: -5 + 5 = 0 0 + -4x = 15 + 5 -4x = 15 + 5 Combine like terms: 15 + 5 = 20 -4x = 20 Divide each side by '-4'. x = -5 Simplifying x = -5
| 4(x+1)5(x+2)= | | 9ln(6x)=63 | | 6x+3(x+7)=-7 | | 2y-17+y=180 | | -3.14y=53.38 | | 7.50h+100=550 | | 2+6h=10+3h | | 47.25x+0.0484=-172.5x+0.4465 | | 24w+(-10)=15 | | 5*3+5*6= | | 90+45=x | | -9x+12=7x+24 | | 5x-18*4=-36 | | A=2(1+w) | | 200m-75m+52800=56100-150m | | 5x-18*4x=-36 | | 32(20x-60)=16(40-x) | | 3(x-5)=2x+9 | | 0.5x=-x+11 | | 2x+4=4x+10 | | 8+z=14 | | 5x-18*x=-36 | | 8x+x=63 | | 2x+4=4x+19 | | -0.125=2(x-1) | | 56t^2-19t=15 | | 32-0.2c=1 | | -13=16+m | | 174x=180(x-700) | | -12n+16=-8n-16 | | 2-p=p+2 | | 5x(x-6)=9+(x-2)(5x-2) |